Pro-active Academic Intervention Strategies for Student Athletes at Southern Methodist University - Swindling, James A. (My University, 1985)
This article reviewed the Student-Athlete Intensive Reading program at SMU, offered to 17 students for one semester based on the results of a Nelson-Denny Reading test as a proactive strategy. Students scores improved on the test after the program, and their GPAs were higher as a result.
Keywords: skills; academic predictors